GlassFish Administration. - Kou, Xuekun (Packt Pub., 2009)
3. Managing Applications on GlassFish; Application management on GlassFish; Java EE applications; Non-Java EE based Java applications; Non-Java applications; Ruby, JRuby, and Rails; Groovy and Grails; Application deployment in GlassFish; Application deployment features of GlassFish; Automatic deployment; Dynamic reload; Directory based deployment; Enable application clients through Java Web Start; Support Plain Old Java Object (POJO) web service; Configuring application libraries; Application deployment tools in GlassFish; Using the asadmin CLI utility; Using the Admin Console.